Análisis descriptivos y visualización de la infraestructura aeroportuaria y terrestre de Colombia desde la iniciativa infraestructura visible (2020)
The Visible Infrastructure initiative of the Universidad de los Andes led by Professor Mauricio Sánchez from the Department of Civil and Environmental Engineering sought a project for a systems engineering student, reflected in this project, to expand the number of data analysis and visualizations that are presented on the website: https://www.infraestructuravisible.org/ particularly focused on the air and land infrastructure in Colombia, since it is in these areas where there is a greater number of possible unexplored analyzes and the were the initiative had the greater interest in conducting data analysis. For the above, it was necessary to raise the requirements of the analysis proposal, perform an exploration on the data that Visible Infrastructure had in terms of roads and airports, list and inquire about the already existing analyzes and propose, implement, and build the visualization of the analyzes accepted by the initiative according to their level of impact and feasibility in the construction of these within 5 months of project development. Through the previous process, three relevant analysis areas were detected, air traffic in Colombia, air coverage of populated centers in Colombia and traffic and collection in tolls and roads in Colombia. For each of them a data quality study was carried out, corrective measures were conducted on them according to the problems of each data set and a control panel was built for each area displayed on a web page where you can see the work done. Finally, the deployment was developed on a web page with the code of the control panels embedded and hosted on Github at the following link: https://a-garcia13.github.io/infraestructuravisible/